Rapid Synthesis of Patterned Silicon Carbide Coatings Using Laser‐Induced Pyrolysis and Crystallization of Polycarbosilane. Issue 7 (7th February 2022) - Anas, Muhammad; Cao, Huaixuan; Oh, Ju Hyun; Sarmah, Anubhav; Long, Carolyn T.; Khan, Mohammad U. F.; Raiman, Stephen S.; Radovic, Miladin; Green, Micah J.
Abstract : The conversion of preceramic polymers to ceramics normally requires multiple processing steps such as curing, pyrolysis, and crystallization, which can be time and energy‐consuming. Herein, one‐step rapid synthesis of cubic silicon carbide (β‐SiC) by laser‐assisted pyrolysis and crystallization of molten polycarbosilane (PCS) is shown. The resulting product is termed as "LISiC" (laser‐induced silicon carbide). It is demonstrated that repeated polymer infiltration and lasing can be used to make dense LISiC and SiC‐LISiC coatings, which are stable up to 1073 K in air. It was also demonstrated that LISiC can be patterned on various substrates such as copper, steel, aluminum, and silicon wafer with a rate of 3 cm 2 min −1 . Finally, it is found that the dense LISiC coatings rapidly heat up in response to radio frequency (RF) fields, which would enable out‐of‐oven manufacturing of SiC‐based composites, micro‐heaters, and efficient chemical synthesis in reactors employing SiC‐based catalyst supports. Abstract : Molten preceramic polymer is rapidly converted into ceramic using a CO2 laser. The technique is useful for the high throughput production of ceramic coatings